The Role of Internship in Shaping Career Self-Efficacy and Career Interest in Islamic Banking - Dewi Rahmawati; Yulia Anggraini; Syaiful Ma’ruf (Falahiya Journal of Islamic Banking and Finance, 2026)
Introduction: The rapid growth of the Islamic banking industry in Indonesia has increased the demand for competent and career-ready human resources. However, job mismatch remains a significant challenge, as data from the National Committee for Islamic Economics and Finance (KNEKS) show that around 90% of workers in the industry do not come from Islamic economics or banking backgrounds. While previous studies have widely examined the influence of internships on work readiness and job interest, limited attention has been given to how internship experiences shape students’ career efficacy in the Islamic banking sector. This study aims to explore the role of student internship activities in enhancing career efficacy and shaping interest in working in the Islamic banking industry. Research Methods: This study employed a descriptive qualitative approach with field research methods. Data were collected through in-depth interviews, observations, and documentation involving Islamic Banking students at UIN Kiai Ageng Muhammad Besari Ponorogo who had completed internship programs in Islamic banking institutions. Results: The findings reveal that internships provide direct exposure to both internal and external banking operations, enabling students to develop practical skills and professional understanding. The main factors contributing to the development of career efficacy include mastery experiences, the presence of professional role models, verbal persuasion from mentors, and emotional management during workplace challenges. The study also found that internship experiences not only strengthen students’ interest in pursuing careers in Islamic banking but also help clarify career preferences when students perceive a mismatch with the industry. Conclusion: Internship experiences play an important role in shaping students’ career efficacy and career interests in the Islamic banking industry. This study contributes to the literature by highlighting internships not only as a medium for career efficacy development but also as a process of career clarification, helping students make more informed career decisions.